2018
DOI: 10.1016/j.fm.2018.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the timing and the nature of nitrogen additions on the production kinetics of fermentative aromas by Saccharomyces cerevisiae during winemaking fermentation in synthetic media

Abstract: During alcoholic fermentation, many parameters, including the nitrogen composition of the must, can affect aroma production. The aim of this study was to examine the impact of several types of nitrogen sources added at different times during fermentation. Nitrogen was added as ammonium or a mixture of amino acids at the beginning of fermentation or at the start of the stationary phase. These conditions were tested with two Saccharomyces cerevisiae strains that have different nitrogen requirements. The addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
43
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 41 publications
17
43
1
Order By: Relevance
“…Nevertheless, significant differences were not found after AF due to the addition of organic nitrogen to the must (Table 2) compared to control. These data differ from those obtained in the same conditions by Seguinot et al [23] who found that organic nitrogen addition significantly increased the production of propanol and isoamyl acetate, even more than ammonium addition. Differences with our results could be due to the type of nitrogen used in both studies.…”
Section: Aromatic Composition Of Winescontrasting
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, significant differences were not found after AF due to the addition of organic nitrogen to the must (Table 2) compared to control. These data differ from those obtained in the same conditions by Seguinot et al [23] who found that organic nitrogen addition significantly increased the production of propanol and isoamyl acetate, even more than ammonium addition. Differences with our results could be due to the type of nitrogen used in both studies.…”
Section: Aromatic Composition Of Winescontrasting
confidence: 99%
“…These results do not coincide with other studies carried out about this topic, which have reported that nitrogen addition affect fermentation rate either enhancing the fermentation activity or the number of cells [1,10,20]. Varela et al [33] concluded that the increase in viable cell concentrations positively correlated with the increase in fermentation rates and Seguinot et al [23] showed that the nitrogen additions systematically reduced the fermentation duration. However, in another work carried out by López et al [34], in which the addition of different doses (15, 30, and 60 g/hL) of DAP was studied for three consecutive vintages in musts of the Viura variety, the additions did not produce significant modifications neither in the spontaneous fermentative kinetics nor in the number of yeasts.…”
Section: Influence Of Nitrogen Addition On the Development Of Af And Mlfmentioning
confidence: 65%
See 2 more Smart Citations
“…On the other hand, a late addition may prevent the sugar transportation and its assimilation by the yeast cells [22]. The timing and also the nature of nitrogen are important factors on the fermentation kinetics, being the organic source the most adequate in some cases [23]. However, the addition inorganic nitrogen sources, mainly the ammonium chloride and the diammonium phosphate salts, can reduce the slow down fermentation risks and the formation of undesirable sulphur compounds [8,13] and improve the aromatic profile of wines [20].…”
Section: Introductionmentioning
confidence: 99%